Sensibilização comportamental à cocaína e neuroadaptações na via mesocorticolímbica : interação com ontogênese, estresse e ambiente - Marin, Marcelo Tadeu (2009)
We investigated the interaction between ontogeny, stress and environment where the drug is administered on the behavioral sensitization to cocaine and related neuroadaptations. This study was divided in two parts. In the first one we evaluated the behavioral sensitization to cocaine and alterations of glutamate receptors and tyrosine hydroxylase enzyme following repeated cocaine administrations or stress exposure on adolescent rats. These alterations were evaluated from adolescence to adulthood. The results showed that cocaine administration during adolescence produced long-term behavioral sensitization to cocaine until adulthood and increased of GluR1 glutamate receptor subunit in the medial prefrontal cortex. The stress-induced behavioral sensitization was evident during adolescence but did not reach adulthood. In the second part, we evaluated the environmental modulation of behavioral sensitization to cocaine and alterations of CREB and upstream kinases activation in adult rats. The results showed that the expression of cocaine-induced behavioral sensitization was specific to the environment paired with previous cocaine administration. Moreover, the number of neurons with CREB activation in the nucleus accumbens was increased in sensitized animals and specific to the paired environment. Thus, our results add new findings on addiction related alterations in adolescent animals, its long-term effects and the environmental modulation of cocaine behavioral and neuronal sensitization.